Merespon Retorika Populisme: Analisis Naratif Pemberontakan Bilangan 16 dalam Perspektif Manajemen Konflik - Pieter Anggiat Napitupulu (PNEUMATIKOS: Jurnal Teologi Kependetaan, 2026)
This article analyzes Moses' leadership response to populist rhetoric in Numbers 16 and its relevance to conflict management in contemporary church leadership. Employing a qualitative method with a narrative analysis approach to Numbers 16, the study finds that Korah's rebellion was not merely a struggle for authority but also a rhetorical contest that employed narratives of equality and accusations of abuse of power to shape the community's perceptions. In response, Moses demonstrated a leadership pattern characterized by self-regulation and the use of fair procedures, the willingness to clarify accusations against his integrity, and prioritizing the well-being of the community amid a crisis of trust. These findings suggest that leadership legitimacy is grounded not in domination or popularity, but in faithful responsibility for the welfare of the community.